Analytical performance estimation of network‐assisted D2D communications in urban scenarios with rectangular cells. Issue 2 (12th November 2015) - Samuylov, Andrey; Ometov, Aleksandr; Begishev, Vyacheslav; Kovalchukov, Roman; Moltchanov, Dmitri; Gaidamaka, Yuliya; Samouylov, Konstantin; Andreev, Sergey; Koucheryavy, Yevgeni
Abstract: The aggressive spatial reuse of radio resources is considered today as one of the most promising avenues to achieve significant cellular capacity improvements in future fifth‐generation networks. Accordingly, device‐to‐device (D2D) communications are an emerging paradigm that promises to offer these much expected gains without the need for additional investments into the network infrastructure. However, before this attractive technology can be deployed ubiquitously, the research community has to fully understand the extent of its potential performance benefits across typical scenarios of interest. In this work, we consider one such use case of rectangular cells (common for offices, shopping malls, dormitories, etc.) and develop the corresponding analytical methodology for D2D performance evaluation. As our target metric, we employ the signal‐to‐interference (SIR) ratio experienced by a D2D user. To this end, we propose two relatively simple approximations for SIR distribution and hence capture the related parameters, including user throughput. Further, we carefully investigate the most interesting numerical results by making important conclusions on the envisioned operation of our chosen scenario. In particular, we demonstrate that under certain conditions, the SIR behaviour is insensitive to the dimensions of cells, while different propagation exponents 'scale' its density function thus allowing to simplify the characterisation of SIR in a wide range of input parameters. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The emerging concept of device‐to‐device communications in a characteristic urban scenario with rectangular cells is analyzed in the paper. Proposed modelling framework is a powerful tool to estimate the signal‐to‐interference ratio and the data rate distributions analytically without the need for time‐consuming and often prohibitive system‐level simulations. Both considered mathematical models, named 'uplink' and 'downlink', provide reasonable upper bounds on the respective system performance showing the accuracy of about 10% according to the respective simulation data.